Administration of hydrogen-rich water prevents vascular aging of the aorta in LDL receptor-deficient mice. Issue 1 (December 2018) - Iketani, Masumi; Sekimoto, Kanako; Igarashi, Tsutomu; Takahashi, Mayumi; Komatsu, Masaki; Sakane, Iwao; Takahashi, Hiroshi; Kawaguchi, Hideo; Ohtani-Kaneko, Ritsuko; Ohsawa, Ikuroh
Abstract The main cause of arteriosclerosis is atherosclerosis in the aorta. Atherosclerosis is recognized as a chronic inflammatory condition that begins with the dysfunction or activation of arterial endothelium. Low-density lipoprotein (LDL) and especially its oxidized form play a key role in endothelial dysfunction and atherogenesis. Recent studies showed that senescent cells are involved in the development and progression of atherosclerosis, and eliminating senescent cells suppresses the senescence-associated secretory phenotype. We previously reported that molecular hydrogen-rich water (HW) has antioxidant and anti-inflammatory effects in numerous diseases. Here, we used LDL receptor-deficient mice fed a high-fat diet (HFD) for 13 weeks as a model for atherosclerosis and evaluated the effects of continuous administration of HW. The numbers of endothelial cells in the atheroma expressing the senescence factors p16INK4a and p21 decreased in HFD-fed mice given HW compared with HFD-fed mice given control water. Furthermore, macrophage infiltration andTnfα expression in the atheroma were also suppressed. These results suggest that vascular aging can be suppressed by HW.